Impact of Administrative Control on subordinates coherence - سموعي, رفاه فرج; عبد الزهرة, زينة رائد (Journal of Economics and Administrative Sciences, 2014)
Abstract: the system of Administrative Control in organizations meets the need to check on the optimal use and proper resources and conservation to achieve the objectives sought by the organization, hence the system of Administrative Control  is part of the overall system in any organization that has undergone evolution always to be able to keep up with progress in the development of other sciences, and that the growth of coherence between subordinates in the organization means the ability to influence the opinions, ideas and attitudes to change it for directions the organization and its values ​​and this is reflected positively on the coherence of the organization, the researcher interest of the impact of administrative control in the cohesion of subordinates within the Ministry of Labour and Social Affairs and the researcher used a random sample of the total (254) Questionnaires   to measure variables Using package SPSS ready, and most important finding is a correlation extrusive High somewhat between management control and cohesion of subordinates and the level of significantly as well as the existence of the effect of controlled administrative consolidation of subordinates, and the presence of the coherence of professional and social high among subordinates, thus enhancing their performance and their work within the formations of the ministry, the most important recommendation is the need to Ministry's interest in promoting the degree of coherence between subordinates and maximize it and the ministry of making the movements of a cadre between formations ministry for outstanding elite cadres winning high cohesion with all other subordinates below that level to activate these coherence and the transfer of expertise and knowledge in the field.